Persistence of rubellavirus-specific immunoglobulin M and immunoglobulin A antibodies: investigation of successive serum samples with lowered immunoglobulin G concentration. - Hornsleth, A (1975)
The persistence of rubellavirus-specific immunoglobulin (Ig) M and IgA antibodies has been studied in seven patients with primary postnatal rubella infections. Successive blood samples obtained over a period of several years after the onset of disease have been investigated, employing the fluorescent antibody technique and the sucrose gradient centrifugation method. IgM antibodies were found to persist for 4 to 5 weeks after the onset of disease, with only moderate variation being observed with respect to the different patients and the method of investigation being studied. The persistence of IgA antibodies (as examined by the fluorescent antibody technique) varied from a few weeks to several years after the onset of the disease. The detection of IgA antibodies cannot be considered as conclusive for the diagnosis of recent rubella infections.